EXTENTION EFFECTIVITY OF BAUNG FISH FARMING IN LANGGAM VILLAGE PELALAWAN SUBDISTRICT RIAU PROVINCE - Khorizon Alwi; Kusai '; Viktor Amrifo (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
The research was conducted in Langgam Village Pelalawan Subdistrict Riau Province on April 2015. The research was aimed to determine the extent of the effectiveness of fisheries extension activities in the Village Langgam by the survey method. The responden was determined by sensus. The extension activities in the Village Langgam is controlling OP (pests) in fish. Effectiveness of fisheries extension in the Village Langgam not effective it is seen from the stage of knowledge the percentage of responden at the stage of analyzing and integrating only reached 50%, at the stage of attitude the percentage of responden in assessment and organizing stages reached 40%, at the stage skill the percentage of responden in the stage familiar, skilled, and addaptation reaches 50%. Low participation of fish farmers to events held by PPL become a problem being constrained of counselling actifity.Keywords : Actifity Counseling, Counseling Effectiveness, Fish Farmers